Effects of antimicrobials on broiler chicken performance - Schmidt, Darby L.; Delfelder, C.J.; Beyer, R. Scott; Stark, Charles R.; Evans, C.E.; Yoder, Ashton D.; Jones, Cassandra K. (My University, 2017)
With concerns increasing over feeding antimicrobials to poultry, alternatives to these feed rations are desired. An alternative that increases digestibility in poultry is needed. Exogenous xylanase is known to increase digestibility in poultry, yet it is unknown if it is able to replace an antimicrobial such as monensin sodium. The objective of this research was to evaluate the digestibility of different diets at different fiber levels, when xylanase replaced monensin sodium. The 21-day experiment included 216 Cobb broiler chicks housed in battery cages with 6 birds/cage, with 6 treatments, and 10 cages/treatment. The treatments included: 1) Corn-based with no monensin sodium or xylanase; 2) wheat-based with no monensin sodium or xylanase; 3) corn-based with monensin sodium but no xylanase; 4) wheat-based with monensin sodium but no xylanase; 5) corn-based with xylanase but no monensin sodium; 6) wheat –based with xylanase but no monensin sodium. Data was collected weekly by measuring pen weights and feed consumption. Total feed intake, body weight gain, and FCR were measured. GLIMMIX procedure of SAS was used and the cage as the experimental unit and the treatment as the fixed effect. The results of the project led to the conclusion that feed intake, BW, and FCR were all effected by the treatments. When comparing diets FCR was not impacted (P>0.05) in the monensin sodium wheat-based diet or the corn-based diet with either monensin sodium or xylanase. When comparing the control diets, the corn-based diet improved (P<0.05) compared to the wheat-based diet. Through this experiment, the conclusion was drawn that FCR is comparable between the corn-based diet and the wheat-based diet with xylanase due to increased carbohydrate digestibility. Due to the battery cages used there was little to no need for an antimicrobial to be fed in the broiler chick diet.
Keywords: Spring 2017